Tradition and modernity in silko’s ceremony and naylor’s mama day: an ecocritical approach - Hesty Nur Aini; Ali Mustofa; Pratiwi Retnaningdyah (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
Ecocriticism is defined as “the study of the relationship between literature and the physical environment” (Glotfelty, 1996: 18). The culture is the impact of human and their beliefs in how they live and how they benefit the environment.Thus, ambivalence related to the change of the culture characterizes the people (Bhabha, 1998: 12). This study uses ecocriticism approach aiming to answer questions: 1) How is human and nature relationship represented in Silko’s Ceremony and Gloria Naylor’s Mama Day?; and 2) How does the relationship reveal conflict between tradition and modernity? There are underlined points need to emphasize from both novels of Silko’s Ceremony and Gloria Naylor’s Mama Day through ecocriticism approach. The first is humans’ attitudes toward nature can be either nurturing or destructing. The second is the conflict between tradition and modernity which is underlying this study parted into two, mainly the differences of tradition and modernity and the crashes between both cultures which involve humans and their attitudes toward nature. Tradition and modernity – as cultures here are seen as result of human and nature co-existence. The last point is the impacts of tradition and modernity. The notable impacts from cultures as the effect of human and nature correlation are ambivalence and conformity